Diversity of phyllospheric Actinomycetes in Liliaceae plants and their potential as growth inhibitors of Alternaria porri - CHEPPY WATI; ABDJAD ASIH NAWANGSIH; ARIS TRI WAHYUDI; SURYO WIYONO; ABDUL MUNIF (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wati C, Nawangsih AA, Wahyudi AT, Wiyono S, Munif A. 2023. Diversity of phyllospheric Actinomycetes in Liliaceae plants and their potential as growth inhibitors of Alternaria porri. Biodiversitas 24: 5234-5242. Actinomycetes are microorganisms belonging to a group of Gram-positive bacteria, that have the potential to act as biological control agents against various plant pathogens. Phyllospheric Actinomycetes particularly, can inhibit growth of various microorganisms, such as the fungus Alternaria porri Ell. Cif., which causes purple blotch disease in the shallot plants. These microbes thrive on the surface of leaves, particularly in plants belonging to Liliaceae family. Environmental conditions have been proven to greatly affect their diversity. Present investigation aims to determine diversity of phyllospheric Actinomycetes from Liliaceae plants and their potential to inhibit growth of A. porri. The methods used were to investigate, characterize, and quantify isolates from Liliaceae plants. An antagonistic test was conducted on the isolates to examine the proportion of A. porri fungus growth inhibition. The results showed that plants species Allium fistulosum and A. tuberosum were the most common hosts for phyllospheric actinomycetes. Morphological differences were found in shape, color, elevation, edges, surface, and hyphae size, as well as the type of spore violation. The surface texture of colonies was smooth, rough, powdery, and opaque, usually appearing after 7-12 days of isolation. The isolates also inhibited growth of A. porri, causing the mycelium thins, and a clear zone of inhibition between pathogens and Actinomycetes forms. Isolates BCW9 caused the highest suppression of fungus growth 57.78%. This study is the first experiment to evaluate the diversity of phyllosphere Actinomycetes from Liliaceae plants, which are able to control purple blotch disease caused by A. porri in Indonesia. The phyllospheric Actinomycetes were isolated from the same habitat of A. porri. These investigation show the prospect of phyllospheric Actinomycetes as biocontrol agents against another fungal diseases on leaves of another plants.